Inovasi SIGRA (Satgas Inspiratif Gerakan Ramah Anak) sebagai Upaya Penguatan Karakter Disiplin Murid Sekolah Dasar - Hendra Santoso; Hitta Alfi Muhimmah; Raden Roro Nanik Setyowati (Patria Educational Journal (PEJ), 2026)
Disciplined character is an essential aspect of personality development among elementary school students. This study aims to describe the need for developing and designing SIGRA (Inspirational Child-Friendly Movement Task Force) as an innovation to strengthen students’ discipline character at SDN Wonokusumo VI/45 Surabaya. The study employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving the principal, teachers, and students selected through purposive sampling. Data were analyzed using the Miles and Huberman interactive model. The findings revealed that disciplinary problems, such as tardiness, bullying, and classroom misconduct, were still prevalent despite the implementation of various character education programs. Furthermore, the existing programs had not optimally involved students as agents of change. Therefore, SIGRA was developed by integrating the concepts of student agency, peer leadership, and positive school culture to encourage students’ active participation in fostering disciplinary habits. The findings contribute to the development of a more participatory, sustainable, and child-friendly character education model in elementary schools. Keywords: SIGRA, discipline character, positive school culture, student agency, elementary school.